Staatsdenker im 17. und 18. Jahrhundert: Reichspublizistik, Politik, Naturrecht - Stolleis, Michael; Hammerstein, Notker (Metzner, 1987)
Michael Stolleis (Hrsg.): "Staatsdenker im 17. und 18. Jahrhundert". Reichspublizistik, Politik, Naturrecht. Alfred Metzner Verlag, Frankfurt/M. 1987. 366 S., 49,80 DM